Sum-Rate Analysis of Intelligent Reflecting Surface Aided Multi-User Millimeter Wave Communications System. Issue 1 (May 2021) - Sur, Samarendra Nath; Singh, Arun Kumar; Kandar, Debdatta; Bera, Rabindranath
Abstract: Intelligent reflecting surface (IRS) is emerging as one of the potential solutions for the future generation communication system. By exploiting a controllable large number of passive elements, IRS is envisioned to provide a high spectral and energy-efficient network. For successful implementation of IRS, it is required to have optimization at a different level and here, this paper analyzed the sum-rate performance of a IRS assisted multi-user(MU) millimeter wave(mmWave) system by exploiting the joint optimization of the active and passive beamforming. Here in this paper, we have considered zero-forcing (ZF) and minimum mean square error(MMSE) based linear precoder. Through the simulation, we have demonstrated the achievable gain due to optimization, and also a relative performance comparison between the precoders is also presented.